(untitled) (Journal of Namibian Studies : History Politics Culture, 2024)
After the great spread of the sport of bodybuilding at the global level in general and African in particular, and as a specialist in this game as a fitness and bodybuilding trainer, we decided to study this topic using a proposed training programme to increase body muscle mass in bodybuilders, which is a goal for all athletes to be more agile and slender. To address this issue, a purposive sample of 18 practitioners was selected and divided into two samples of 9 practitioners each, a control group working with the traditional training programme and the other experimental group working with the proposed training programme. We observed that the experimental sample witnessed a significant improvement and development compared to the control sample that worked with the traditional programme, and this is due to the effectiveness of the proposed training programme based on correct scientific foundations, taking into account all matters that the game is subject to, whether training and exercises, dietary programme, or matters related to rest and recovery. The results of the post-tests between the control and experimental groups showed a positive development in favour of the experimental sample, according to the proposed training programme that used various modern training techniques.